Fundamentals of Entrepreneurship (ENT300) Business Plan: Vinc Pekasam Ikan / Nicko Clinton Jennau ak Edmond - Edmond, Nicko Clinton Jennau; Betti, Clarence Neathen; Peter Chin, Isma; Sakai, Veneta Keren (2017)
VINC Company are aim to be the trusted for producing Perkasam Ikan that is Malaysian traditional food. To be trusted, administration should conduct, lead and take care of their business and staff that work in the company so the employees and the business run smoothly and gaining profit. The management will make sure their worker will welfare guaranteed. The role of administration department also help assisting each employee by determine the equipment and personal needed to run the business efficiently. This department also plays its role to play a selection and bring a good look to create a standard of specification. An etiquette must have in the VINC Company because it is the standard of administrative objective. Employees need to be committed and honest toward their job. Administrative manager will conduct and gives the instruction on doing their work. Administrative manager will record what happen in the company and outside to related with the company besides helping the company.